APPRECIATIVE LEADERSHIP TRANSFORMATION: CULTIVATING POSITIVE CULTURE AND ENHANCING COLLECTIVE PERFORMANCE IN EDUCATIONAL SETTINGS - Muh. Takdir; Apit Dulyapit (MADINASIKA, 2025)
This study aims to explore the practice of appreciative leadership in school settings and its impact on the development of a positive culture and the enhancement of collective performance. Employing a qualitative approach with an intrinsic case study design, the research involved principals and teachers from primary and secondary education institutions in Jakarta, Indonesia, as research subjects. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analysed using inductive thematic techniques. The findings revealed five key themes: (1) appreciation functions as a driver of a positive school culture; (2) reflective and empathic communication serves as the foundation of effective leadership; (3) teacher empowerment is carried out through trust and the delegation of strategic responsibilities; (4) appreciative social relations foster collective teacher efficacy; and (5) the alignment between leaders’ personal values and the school’s organizational culture strengthens leadership effectiveness. These findings reinforce previous literature on appreciative leadership, compassionate leadership, and emotional regulation in educational leadership. The study contributes to the development of a contextual, reflective, and well-being-oriented conceptual framework of appreciative leadership in education. Future research is encouraged to employ longitudinal and quantitative approaches to enhance the validity of findings and examine the broader impact of leadership on student learning outcomes.